THE EXTRACTIVISM IN LATIN AMERICA AND ITS THEOLOGICAL DIMENSION FROM A DECOLONIAL FACE - Aguilar García, Elizabeth Gabriela (2019)
The effects of extractive practices in Latin America have been devastating for the envi- ronment and the health of the surrounding communities. The search for solutions to this problem can not be reduced to a simply change between governments of the left and the right, since both are derived from the same Western-centric paradigm of the world that conceives nature as a source of wealth to explode, legitimized by the Bible and secularized in the idea of progress. We propose a decolonial perspective that considers the learning of other worldviews and ways of relating to nature, whose central axis is the maximum respect of human and non-human life, taking up intra and extra-western knowledge in a fraternal dialogue between different cultures, which will lead to the creation of a new non-imperial civilization that respects the diversity of life on the planet.